2021
DOI: 10.1016/j.cegh.2021.100743
|View full text |Cite
|
Sign up to set email alerts
|

Critical analysis of drug related problems among inpatients in the psychiatry department of a tertiary care teaching hospital: A pharmacist led initiative

Abstract: Introduction: Drug Related Problems (DRPs) frequently take place in modern medical practices, increasing the morbidity and mortality as well as the cost of patient care. Objective: The current study was undertaken to identify and evaluate various DRPs among the inpatients of the psychiatry department in a tertiary care teaching hospital using APS-Doc classification system and to identify the most recurrent drugs causing the DRPs. Method: ology: A prospective observational study was conducted forduration of six… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 14 publications
(12 reference statements)
0
6
0
Order By: Relevance
“…Several studies have previously examined DRPs in hospitalized patients (11,(21)(22)(23); however, few data are available from regular community pharmacies (24). While we found our most common DRPs, studies with predominantly inpatient settings have shown that DRPs such as the need for a new medication or dose increase (9), suboptimal drug effect (22), and lack of therapy (25) are signi cant problems in inpatients.…”
Section: Discussionmentioning
confidence: 70%
See 1 more Smart Citation
“…Several studies have previously examined DRPs in hospitalized patients (11,(21)(22)(23); however, few data are available from regular community pharmacies (24). While we found our most common DRPs, studies with predominantly inpatient settings have shown that DRPs such as the need for a new medication or dose increase (9), suboptimal drug effect (22), and lack of therapy (25) are signi cant problems in inpatients.…”
Section: Discussionmentioning
confidence: 70%
“…Several studies have demonstrated pharmaceutical care's effectiveness in all settings (9)(10)(11). In particular, research shows that pharmacist medication review can positively impact adherence, improve prescription appropriateness, and potentially reduce emergency department visits.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the current finding also showed that lesser prevalence of ADR than studies done in India and Japan, 43.5% and 63%, respectively. 3,29 The possible reason is due to the setting difference (outpatient versus inpatients), difference in sociodemographic characteristics of the patients and method of assessment of ADR (severity was done using the modified Hartwig and Siegel scale), but in this study, severity was not determined.…”
Section: Discussionmentioning
confidence: 94%
“…Polypharmacy, as a common practice in psychiatry ( 9 ), increases the risk for drug-related problems including adverse drug reactions ( 10 , 11 ). The Pharmaceutical Care Network Europe (PCNE) defines a drug-related problem (DRP) as an event or circumstance involving drug therapy that actually or potentially interferes with desired health outcomes ( 12 ).…”
Section: Introductionmentioning
confidence: 99%